A CreER mouse to study melanin concentrating hormone signaling in the developing brain. Issue 8 (11th September 2018) - Engle, Staci E.; Antonellis, Patrick J.; Whitehouse, Logan S.; Bansal, Ruchi; Emond, Michelle R.; Jontes, James D.; Kesterson, Robert A.; Mykytyn, Kirk; Berbari, Nicolas F.
Summary: The neuropeptide, melanin concentrating hormone (MCH), and its G protein‐coupled receptor, melanin concentrating hormone receptor 1 (Mchr1), are expressed centrally in adult rodents. MCH signaling has been implicated in diverse behaviors such as feeding, sleep, anxiety, as well as addiction and reward. While a model utilizing the Mchr1 promoter to drive constitutive expression of Cre recombinase (Mchr1‐Cre) exists, there is a need for an inducible Mchr1‐Cre to determine the roles for this signaling pathway in neural development and adult neuronal function. Here, we generated a BAC transgenic mouse where the Mchr1 promotor drives expression of tamoxifen inducible CreER recombinase. Many aspects of the Mchr1‐Cre expression pattern are recapitulated by the Mchr1‐CreER model, though there are also notable differences. Most strikingly, compared to the constitutive model, the new Mchr1‐CreER model shows strong expression in adult animals in hypothalamic brain regions involved in feeding behavior but diminished expression in regions involved in reward, such as the nucleus accumbens. The inducible Mchr1‐CreER allele will help reveal the potential for Mchr1 signaling to impact neural development and subsequent behavioral phenotypes, as well as contribute to the understanding of the MCH signaling pathway in terminally differentiated adult neurons and the diverse behaviors that it influences.